1975
DOI: 10.1084/jem.142.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of in vitro antibody synthesis by immunoglobulin-binding factor.

Abstract: Alloantigen-activated mouse T cells secrete a factor which binds to the Fc fragment of IgG and blocks complement (C) activation by IgG (immunoglobulin-binding factor, IBF). IBF was found to suppress the direct plaque-forming cell (PFC) response of mouse spleen cell cultures to sheep erythrocytes and to dinitrophenylated aminoethyldextran (T-independent antigen). Purification of IBF by affinity chromatography on IgG-coated Sepharose columns led to an increase of the suppressive capacity with IgG, IgM, or Fab2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Fab fraction-mediated efficiency of pooled human IgG might be explained by anti-idiotypic activity against autoantibodies [11][12][13][14][15][16], by modulation of B and T lymphocyte functions through binding to these cells [16][17][18][19][20][21], by recognition and elimination of infectious agents associated with autoimmune diseases [10,22], or by modulation of the activity of various lymphokines, including IL-1, IL-6 and tumour necrosis factor (TNF) [23][24][25][26]. Through their Fc region, IgG could, among other possible mechanisms [7], increase the catabolism of autoantibodies [10], or decrease antibody production, via the production of soluble Fc receptors [27][28][29][30][31]. However, one of the most probable mechanisms that could explain the therapeutic activity of IgG pools is a temporary blockage of Fc receptors on phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fab fraction-mediated efficiency of pooled human IgG might be explained by anti-idiotypic activity against autoantibodies [11][12][13][14][15][16], by modulation of B and T lymphocyte functions through binding to these cells [16][17][18][19][20][21], by recognition and elimination of infectious agents associated with autoimmune diseases [10,22], or by modulation of the activity of various lymphokines, including IL-1, IL-6 and tumour necrosis factor (TNF) [23][24][25][26]. Through their Fc region, IgG could, among other possible mechanisms [7], increase the catabolism of autoantibodies [10], or decrease antibody production, via the production of soluble Fc receptors [27][28][29][30][31]. However, one of the most probable mechanisms that could explain the therapeutic activity of IgG pools is a temporary blockage of Fc receptors on phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to negative signals, T suppressor cells that preferentially inhibited IgA (4), IgE (5), and IgG2a and IgG2b (6) plaqueforming cells (pfc) were reported. Immunoglobulin-binding factor(s) [IBF(s)] that inhibit the differentiation of B cells to pfc have been described (7,8). Further studies of this factor by Fridman et al (9) demonstrated that IBF is the soluble form of Fcy receptor expressed on a T-cell subset.…”
mentioning
confidence: 99%
“…Considerable evidence has been recently accumulated indicating that FcR ÷ cells participate significantly in regulating isotypespecific antibody responses. Suppressor T cells and their released soluble products, some of which are immunoglobulin-binding factors (IBF), that selectively inhibit synthesis of IgG~, IgG~a, and IgG2b have been demonstrated by other investigators (38,39). Similarly, in the IgA system FcRo~ + T cells generated in high quantities in IgA myeloma-bearing mice, have been shown to regulate the synthesis of IgA (40).…”
Section: Discussionmentioning
confidence: 98%